Real-time lymphography by indocyanine green fluorescence: improved navigation for regional lymph node staging - Hirche, Christoph; Engel, Holger; Kneser, Ulrich (Annals of plastic surgery, 2014)
Objectives : Lymphatic imaging is an important step for the identification of lymphonodal positive disease in solid malignancies. Various methods have been established to detect positive lymph nodes, but the available diagnostic tools leave some inherent drawbacks. The aim of this study was to validate the indocyanine green (ICG) guided approach for transcutaneous and transmesenterial navigation with accurate lymph vessel and node identification for regional lymph node staging in solid malignancies. Methods: After institutional review board approval, a planar fluorescence imaging system was applied for lymphography and lymph node detection using ICG. A total of 96 patients were recruited and subject to fluorescence navigation for axillary (n = 46), inguinal (n = 16), and mesenterial (n = 34) visualization to analyze technical and clinical feasibility of the method after regional lymph node dissection and the applicability. Results: Overall fluorescence imaging identified lymphatic vessels and the SLN in 92 out of 96 patients (detection rate: 96%) after a mean injection of 7 mg ICG. Sensitivity based on fluorescent emission of ICG navigation was 95.6% in 65 out of 68 patients with lymph node dissection. All solid tumors were feasible for fluorescence-guided navigation with a broad spectrum. Conclusion: Fluorescence-guided real-time lymphography with navigation to regional lymph nodes enables accurate visualization for a broad spectrum of different solid tumors with potential lymphonodal spread. In addition, the technique can be applied for lymphography in non-malignant diseases. With reference to the broad application spectrum, institutional investment in camera equipment can be justified.